2012
DOI: 10.1001/archgenpsychiatry.2012.191
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Common Variants Near the Melanocortin 4 Receptor Gene and Severe Antipsychotic Drug–Induced Weight Gain

Abstract: Context Second-generation antipsychotics (SGAs) are increasingly used in the treatment of many psychotic and non-psychotic disorders. Unfortunately, SGAs are often associated with substantial weight gain, with no means to predict which patients are at greatest risk. Objective To detect alleles of single nucleotide polymorphisms (SNPs) associated with antipsychotic drug-induced weight gain. Design Pharmacogenetic association study Setting Discovery cohort was collected at a U.S. general psychiatric hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 31 publications
3
114
0
2
Order By: Relevance
“…145 A GWAS in a cohort of drug-naive adolescents showed significant association of an SNP near this gene with weight gain induced by several APs, which was replicated independently by our group. 146 In a different study, our group has also shown a significant association of another SNP in the promoter region of MC4R with AIWG. 147 A recent GWAS found significant associations of AIWG with SNPs in the Meis homeobox 2 (MEIS2), protein kinase, cyclic adenosine monophosphate-dependent, regulatory, type II, beta (PRKAR2B), G protein-coupled receptor 98 (GPR98), formin homology 2 domain containing 3 (FHOD3), ring finger protein 144A (RNF144A), astrotactin 2 (ASTN2), sex determining region Y-box 5 (SOX5), and activating transcription factor 7 interacting protein 2 (ATF7IP2) genes 148 but these findings have not yet been replicated in other studies.…”
mentioning
confidence: 77%
“…145 A GWAS in a cohort of drug-naive adolescents showed significant association of an SNP near this gene with weight gain induced by several APs, which was replicated independently by our group. 146 In a different study, our group has also shown a significant association of another SNP in the promoter region of MC4R with AIWG. 147 A recent GWAS found significant associations of AIWG with SNPs in the Meis homeobox 2 (MEIS2), protein kinase, cyclic adenosine monophosphate-dependent, regulatory, type II, beta (PRKAR2B), G protein-coupled receptor 98 (GPR98), formin homology 2 domain containing 3 (FHOD3), ring finger protein 144A (RNF144A), astrotactin 2 (ASTN2), sex determining region Y-box 5 (SOX5), and activating transcription factor 7 interacting protein 2 (ATF7IP2) genes 148 but these findings have not yet been replicated in other studies.…”
mentioning
confidence: 77%
“…However, a recent genetic study reported that neither the POMC single nucleotide polymorphisms (SNPs) (rs6713532, rs1047521, rs3754860) nor the CART SNP (rs10515115, rs3763153, rs3857384, rs11575893, rs16871471) gene variants was associated with weight gain in chronic schizophrenia patients treated with SGAs [162]. On the other hand, a genetic polymorphism study suggested that MC 4 R is relevant to SGA-induced weight gain and related metabolic disorders [163].…”
Section: The Role Of Pomc and Cart In Sga-induced Weight Gainmentioning
confidence: 99%
“…A GWAS has recently identified marker rs489693, approx. 200 kb downstream of the MC4R gene to be associated with AIWG (125). Given that this finding was replicated across various samples in different populations using different APs, a major role for rs489693 is likely in AIWG (125Á127).…”
Section: Pharmacodynamicsmentioning
confidence: 70%